Banana stem juice protected soy bean meal as feed suplement to sheep: In sacco and in vivo - W Puastuti; I-W Mathius; D Yulistiani (Jurnal Ilmu Ternak dan Veteriner, 2006)
Protein with low resistant of rumen degradability must be protected, which part of its protein could reach post ruminal and able to supply amino acids for ruminant. The experiment was conducted to obtain the best ratio of soy bean meal with banana stem juice as feed supplement protecting protein. Rumen degradability using rumen fistulated sheep were evaluated in saccous at incubation times of 0, 2, 4, 6, 12, and 24 hours.  The best ratio in the in sacco experiment was used for further in vivo experiment. Fifteen growing lambs with average live weight of 18.6 ± 2.2 kg were grouped according to body weight in trial with a simple randomized design. Three treated rations were R0 = control diet with 0% protected soy bean meal, R50 = diet with 50% protected soy bean meal, and R100 = diet with 100% protected soy bean meal. All diets were iso nitrogen and iso energy (CP 18% and TDN 75%). Diet consisted approximately 30% king grass and 70% concentrate. The experimental diets were offered for 12 weeks. The result from in sacco experiment showed that the best ratio between soybean meal and banana stem juice was 2:1 w/v (R2). This mixture had the highest rumen undegradable dry matter and protein. Result from in vivo experiment showed that the intake and digestibility of dry matters, the intake and digestibility of crude protein. The intake and digestibilities of dry matter intakes and digestibilitie of crude protein, pH value, NH3-N, total bacteria, purin and total VFA in rumen fluid were not affected by feed supplement. The same average body weight at the beginning of study resulted same body weight at the end of study. The ADG of R50 and R100 (138.1 and 122.2 g) were respectively not different with the control, RO (120.9g). It was concluded that soy bean meal and banana stem juice 2:1 w/v was the best ratio, but as feed supplement with high resistant rumen degradable protein can not produce higher growth rate than the control group. Key Words: Soy Bean Meal, Banana Stem Juice, Protected Protein, Degradation